Peran Ki Warsono Plonk dalam Menyebarkan Nilai Islam Nusantara melalui Seni Wayang di Kecamatan Mojowarno Jombang - Aulia, Farina Fikria; Khoiruddin, Untung (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2025)
The adaptability of universal religious values has long enabled local wisdom, such as Wayang, to play an important role in the internalization of Islamic values in Indonesia. Therefore, this article aims to explore Ki Warsono Plonk’s internalization of Islam Nusantara values through Wayang performances, da’wah strategies, and the implications for society. The study employs a qualitative case study design through interviews, observation, and documentation. Data analysis shows that Ki Warsono Plonk conveys Islamic values through the selection of relevant plays, humorous Punakawan dialogues, Islamic-themed suluk, and direct advice to the audience. Ki Warsono Plonk also successfully balances entertainment and da’wah, ensuring the moral message is well received. The wayang performance has increased the community’s understanding of tolerant Islam and strengthened the preservation of local culture.